Enhanced light scattering with energy downshifting using 16 nm indium nitride nanoparticles for improved thin-film a-Si N-i-P solar cells - ALEVLİ, MUSTAFA (Electrochemical Society Inc., 2015)
In this work the effect of Indium nitride (InN) nanoparticles (NPs) on the performance of a-Si: H solar cells has been investigated. The average Jsc of InN NPs coated cells was found 6.76 mA/cm2 which is 16.69% higher than the average Jsc of the reference cell which was 5.79 mA/cm2. Average efficiency of InN NPs coated cells showed 14.16% increase from 3.32% to 3.79%. Peak EQE has increased from 44.8% at 500 nm to 51.67% at 510 nm and peak IQE has increased from 51.70% at 510 nm to 68.38% at 500 nm for InN NPs coated cell. Further study shows that EQE change is larger between 510 nm-700 nm compared to IQE change indicting a surface scattering mechanism that reduces the reflectivity. However, between 400 nm-510 nm IQE change is larger than EQE change which indicates that energy downshifting mechanism is dominating. So overall performance enhancement can be attributed to the scattering and photoluminescence properties of InN NPs that enhances absorption inside a-Si: H solar cells. © The Electrochemical Society.